2020
DOI: 10.3389/fbioe.2020.00407
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Metabolically Engineered Microorganisms for the Production of Aromatic Chemicals Derived From Aromatic Amino Acids

Abstract: Aromatic compounds derived from aromatic amino acids are an important class of diverse chemicals with a wide range of industrial and commercial applications. They are currently produced via petrochemical processes, which are not sustainable and eco-friendly. In the past decades, significant progress has been made in the construction of microbial cell factories capable of effectively converting renewable carbon sources into value-added aromatics. Here, we systematically and comprehensively review the recent adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 167 publications
(232 reference statements)
0
26
0
Order By: Relevance
“…In our previous paper [ 13 ], applying a combinatorial strategy of the directed evolution of pathway enzymes and quorum-sensing-based dynamic regulation of the pathway further improved the production of 4HPAA, which reached 17.39 g/L in 2-L bioreactor fed-batch fermentation. However, the titer of 4HPAA in engineered microorganisms is much lower than that of other aromatic compounds [ 14 ]. Thus, further work is required to increase the production of 4HPAA.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous paper [ 13 ], applying a combinatorial strategy of the directed evolution of pathway enzymes and quorum-sensing-based dynamic regulation of the pathway further improved the production of 4HPAA, which reached 17.39 g/L in 2-L bioreactor fed-batch fermentation. However, the titer of 4HPAA in engineered microorganisms is much lower than that of other aromatic compounds [ 14 ]. Thus, further work is required to increase the production of 4HPAA.…”
Section: Introductionmentioning
confidence: 99%
“…Even if all belong to the recombinant protein of Rg PAL/TAL, the K m values for substrates l -Phe and l -Tyr were quite different. Obviously, the K m for TAL observed in this study indicated its high affinity to l -Tyr substrate, which would be valuable to produce a wide range of aromatic compounds that using l -Tyr or its derivative as a precursor (Shen et al, 2020 ).…”
Section: Resultsmentioning
confidence: 73%
“…The data represent means of three replicates and error bars represent standard deviations. Shen et al, 2020). Aguilar et al (2012Aguilar et al ( , 2015 reported that deletion of the 2-acyl-glycerophosphoethanolamine cycle allows fast growth in glucose and improves the production of aromatic compounds in E. coli strain lacking the phosphoenolpyruvate: carbohydrate phosphotransferase system (PTS).…”
Section: Host Strain Engineering Increasing the Availability Of L-tyrosinementioning
confidence: 99%